Relationship between the adenosine A1 receptor and cGMP levels in the hippocampus: implications on neurotransmission and synaptic plasticity - Serpa, André Santos Romão Piques (2016)
The cyclic nucleotides cAMP and cGMP are second messengers whose levels are modulated by G proteins-coupled receptors, and regulate multiple brain functions, including neurotransmission, memory and synaptic plasticity. The adenosine A1 receptor is highly expressed in the hippocampus where it inhibits neurotransmitter release, protects against excitotoxic insults and regulates synaptic plasticity. Adenosine A1 receptor is coupled to Gi/o proteins which negatively regulate adenylyl cyclase and thus cAMP formation. Modulation of cGMP levels by Gi/o proteins-coupled receptors has also been recently reported. In the present work the ability of adenosine A1 receptors to regulate cyclic nucleotides levels in the hippocampus was investigated. The role of cyclic nucleotides as mediators of some actions of adenosine A1 receptor in the hippocampus was also studied. Activation of adenosine A1 receptor has been shown to decrease cAMP formation in the cerebral cortex, but its effect on cAMP levels at the hippocampus is not clarified, nor its interaction with others neuromodulators while regulating cAMP levels. We set forth to determine the type of interaction found between adenosine A1 and cannabinoids CB1 receptors as negative modulators of cAMP accumulation. Furthermore, we also intend to explore their combined neuroprotective potential. Quantification of cAMP in hippocampal slices was performed through an enzymatic immunoassay, while neuroprotection against NMDA-induced toxicity was assessed by determination of released LDH activity and by quantification, by fluorescence microscopy, of the uptake of propidium iodide (PI) in cultured organotypical hippocampal slices. The A1 agonist N6-Cyclopentyladenosine (CPA) decreased forskolin-stimulated cAMP accumulation in the hippocampal slice with an EC50 of 35 ± 19 nM and an Emax of 29% ± 5%, whereas for the CB1 agonist, WIN55212-2, an EC50 of 6.6 ± 2.7 μM and an Emax of 31% ± 2% were obtained. NMDA (50 μM) increased the release of LDH activity by 92% ± 4% (n=4) when compared with control. Application of WIN55212-2 (30 μM) decreased NMDA-induced LDH activity by 53% ± 11% (n=4), while CPA (100 nM) decreased it by 37% ± 11% (n=4). The combined inhibitory effect of WIN55212-2 (30 μM) and CPA (100 nM) on cAMP accumulation (41% ± 6%, n=4) and NMDA-induced LDH release (88% ± 14%, n=4) did not differ from the sum of the individual inhibitory effects of each agonist (43% ± 8%, n=4, for cAMP accumulation and 90 % ± 22%, n=4, for LDH release), but was different from the effects of CPA or WIN55212-2 alone. Similarly, an additive inhibitory effect of co-application of WIN55212-2 (30μM) and CPA (100nM) on NMDA (50μM)-induced PI uptake was also observed in CA3 but not in CA1 area of the hippocampal slice. Thus, the combined effect of CB1 and A1 agonists on cAMP accumulation and NMDA-induced neurotoxicity is additive suggesting that both agonists trigger independent cAMP signalling pathways and produce independent cumulative neuroprotection against excitotoxic insults in the hippocampus. Previous studies indicate that cGMP produces similar effects to those triggered by adenosine A1 receptors and, recently, it was reported that cGMP might mediate some actions of adenosine A1 receptor in the peripheral nervous system. However, the role of cGMP on adenosine A1 receptor mediated activity at the central nervous system remains obscure. Our aim was to clarify if cGMP is modulated by A1 receptors at the hippocampus, if this modulation depends on activation of the soluble form of guanylyl cyclase, and if such mechanism is identical between male and female rats. Furthermore, the role of cGMP in mediating the inhibitory effect of adenosine A1 receptor on neurotransmission in the hippocampus was also investigated. To achieve our objectives, we used two approaches, enzymatic immunoassays to measure cGMP accumulation and extracellular electrophysiology to measure synaptic transmission at the rat hippocampal slice. The enzymatic immunoassays tests reveal that application of CPA increased cGMP accumulation with an EC50 of 4.2 ± 1.4 nM and an Emax of 17% ± 0.9%. Furthermore, in male rats, the presence of sodium nitroprosside (SNP, a nitric oxide donor) abolished the effect of CPA on cGMP accumulation. In contrast, in female rats, SNP failed to modify the increase in cGMP accumulation induced by CPA, but this increase was reversed by DPCPX, stressing that A1 receptors modulate cGMP accumulation despite the increase in soluble guanylyl cyclase activity by SNP. Thus, A1 receptors increase intracellular cGMP levels at the hippocampus, through mechanisms which differ according to gender. Regarding extracellular electrophysiology studies, we investigated in what extent blocking the cGMP pathway using nitric oxide synthase (NOS), protein kinase G (PKG) and soluble guanylyl cyclase (sGC) inhibitors, would interfere with the inhibitory effect of CPA on synaptic transmission. CPA (15 nM) alone reversibly decreased synaptic transmission by 48% ± 2.1% (n=5) in males and by 54 % ± 5 % in females (n=5). In the presence of the NOS inhibitor LNAME (300 μM), the sGC antagonist ODQ (10 μM) and the PKG inhibitor KT5823 (1 nM), CPAinduced inhibition of synaptic transmission was dampened by 57 % ± 9 % (n=5), 23 % ± 7 % (n=4) and 49 % ± 9 % (n=4), respectively. This attenuation of the effect of CPA was similar in males and females. These findings suggest that A1 receptor neuromodulatory activity on synaptic transmission partially depends on the cGMP pathway.